Impact of cigarette smoking in type 2 diabetes development - Xie Xi-tao; Liu Qiang; Wu Jie; Wakui Makoto (Acta Pharmacologica Sinica, 2016)
Many patients with type 2 diabetes mellitus (DM2) are at risk for micro and macro vascular complications, which could be observed in heavy smokers. Cigarette smoking increases the risk for type 2 diabetes incidence. Nicotine, acknowledged as the major pharmacologically active chemical in tobacco, is responsible for the association between cigarette smoking and development of diabetes. This minireview summarized recent studies on nicotine effects on insulin action and insulin secretion, indicating the impact of nicotine on type 2 diabetes development.